2000
DOI: 10.1002/(sici)1097-4628(20000516)76:7<1100::aid-app14>3.0.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties and creep resistance in polystyrene/polyethylene blends

Abstract: ABSTRACT:Recycled plastics, predominantly high-density polyethylene (PE), are being processed in the shape of dimension lumber and marketed as "plastic lumber." One drawback to these products is their low creep resistance or high creep speed. The objective of this study was to examine the feasibility of reducing the creep speed of PE-based products by blending the PE with a lower-creep plastic, in this case polystyrene (PS). Various blends of PE and PS were prepared in either a laboratory extruder or a bowl mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 21 publications
4
19
0
Order By: Relevance
“…This phenomenon is analogous to the shear yielding of thermoplastic matrix induced by fine rubber particles during impact deformation. 44, 45…”
Section: Resultsmentioning
confidence: 99%
“…This phenomenon is analogous to the shear yielding of thermoplastic matrix induced by fine rubber particles during impact deformation. 44, 45…”
Section: Resultsmentioning
confidence: 99%
“…Better homogeneity of blend was found. In the aPS/HDPE/ SEBS 40/60/5 blend (Figures 3(b) and 4(b)), the dispersed aPS particles were mainly spherical, which can be attributed to higher viscosity of PS [2,3]. The SEBS interface layer was visible.…”
Section: Morphology Of the Blendsmentioning
confidence: 99%
“…It was observed that the creep behavior of all the films was basically controlled by the deformation of the amorphous phase and more specifically, by the density and tautness of tie chains. Xu et al [21] blended high creep PE with low creep polystyrene. They found improved creep resistance in PE/PS blend compared to pure PE.…”
Section: Introductionmentioning
confidence: 99%